Towards quantitative analysis of gene regulation by enhancers. (September 2017) - Nizovtseva, Ekaterina V; Todolli, Stefjord; Olson, Wilma K; Studitsky, Vasily M
Enhancers are regulatory DNA sequences that can activate transcription over large distances. Recent studies have revealed the widespread role of distant activation in eukaryotic gene regulation and in the development of various human diseases, including cancer. Here we review recent progress in the field, focusing on new experimental and computational approaches that quantify the role of chromatin structure and dynamics during enhancer–promoter interactions in vitro and in vivo .